ESL Practicum in Indian Universites Students Face - Sai Kumar, Somanchi (International Journal of Psychosocial Rehabilitation, 2024)
The purpose of this research is to illuminate the challenges faced by ESL students enrolled in practical classes at Indian University. Research participants were second-semester ESL students enrolled in practicum classes. Participants were selected using a proportionate stratified random sampling method. Twenty-five boys and 117 girls made up the student sample. In order to gather information, the researchers created a questionnaire and a semistructured interview. There were 56 questions spread over 6 sections of the survey. Five institutions were chosen, including Dr. BR Ambedkar University, Andhra University, Adikavi Nannayya University, Krishna University, and Dr. BR Ambedkar Open University. According to the findings, the overall difficulty level for ESL students in practical courses at Indian University is moderate. They also demonstrated that gender, GPA, and institution had no discernible effect on respondents’ mean ratings of the difficulties experienced by ESL students doing practicum courses at Indian institutions. There were significant differences in the mean scores at 0.05 between issues faced by ESL students in practicum courses at the university and problems faced by students at other universities in regards to the academic supervisor.